Provisorium Hungaricum: A rendszerváltás heraldikája - Szolnoki, József (Studia Litteraria, 2024)
Each political system creates its own places of remembrance, for example monuments, names, holidays. However, the transition between systems (interregnum) is not institutionalised, and usually lasts for a short period of time, therefore it cannot create official places of remembrance. Or, unintentionally, it does create some. Still, it is in these spontaneous non-places that the transience itself is preserved. Of the painted, pasted, painted over, and knocked down examples, those that are of particular interest are those where it is clear that the aim was not total disappearance. In Hungary, the Kádár coat of arms has survived in the absence of its own image, creating a ritual continuity between the past lived and the past already transformed into history. The double title, representing the ideological superposition of the transitional state separating the two successive regimes, is in fact a heraldic leak through which the double talk seeps from so dictatorship to lukewarm democracy.